2011
DOI: 10.1016/j.pbi.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach to the evolution of plant–virus interactions

Abstract: ElsevierElena Fito, SF.; Carrera, J.; Rodrigo, J. (2011). A systems biology approach to the evolution of plant-virus interactions. Current Opinion in Plant Biology. 14(4):372-377. doi:10.1016/j.pbi.2011.03.013. Omic approaches to the analysis of plant-virus interactions are becoming increasingly popular. These types of data, in combination with models of interaction networks, will aid in revealing not only host components that are important for the virus life cycle, but also general patterns about the way in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…8) with previously known dicot-infecting plant viruses (Whitham et al, 2003;Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Elena et al, 2011;Hanssen et al, 2011) revealed several distinctive features of virus-host interactions of monocots. PMV and PMV+SPMV infection prominently triggered SA-mediated defense responses, a response that appears conserved with several dicot host:virus interactions (Murphy et al, 1999;Kachroo et al, 2000;Whitham et al, 2003Whitham et al, , 2006Huang et al, 2005;Ascencio-Ibáñez et al, 2008;Hanssen et al, 2011;Pacheco et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…8) with previously known dicot-infecting plant viruses (Whitham et al, 2003;Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Elena et al, 2011;Hanssen et al, 2011) revealed several distinctive features of virus-host interactions of monocots. PMV and PMV+SPMV infection prominently triggered SA-mediated defense responses, a response that appears conserved with several dicot host:virus interactions (Murphy et al, 1999;Kachroo et al, 2000;Whitham et al, 2003Whitham et al, , 2006Huang et al, 2005;Ascencio-Ibáñez et al, 2008;Hanssen et al, 2011;Pacheco et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…Because high-quality genome sequence information is available for Arabidopsis, and because antiviral defenses are well studied in that model (Whitham et al, 2003;Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Elena et al, 2011;Hanssen et al, 2011), for our subsequent analysis, we chose to compare our transcriptome results with Arabidopsis-virus responses. Moreover, such a comparison allows us to compare and contrast antiviral responses in monocot and dicot plants.…”
Section: Host Defense Responses To Pmv and Spmvmentioning
confidence: 99%
See 1 more Smart Citation
“…The applications include analyses of the abiotic stress response (Cramer et al, 2011), of the host/pathogen interaction (Elena et al, 2011;Pritchard and Birch, 2011), of nitrogen nutrition (Gutiérrez, 2012), and of general metabolism (Sweetlove et al, 2003).…”
Section: Systems Biological Approach Toward Understanding Plant Metabmentioning
confidence: 99%
“…An excellent and updated review on topology of interaction networks may be found in (Winterbach et al 2013). Some studies have dealt with the topological properties and features of PPINs (Albert and Barabási 2002;Pržulj, Wigle, and Jurisica 2004;Pržulj 2011;Yook, Oltvai, and Barabási 2004), however just a few have focused on viral PPINs (Elena, Carrera, and Rodrigo 2011;Elena and Rodrigo 2012;Fossum et al 2009). Viral infection is a complex process and it requires a systems approach to be fully described.…”
Section: Introductionmentioning
confidence: 99%